2021
DOI: 10.1002/1873-3468.14071
|View full text |Cite
|
Sign up to set email alerts
|

Centrosomal protein FOR20 knockout mice display embryonic lethality and left‐right patterning defects

Abstract: Centrosomal protein FOR20 has been reported to be crucial for essential cellular processes, including ciliogenesis, cell migration, and cell cycle in vertebrates. However, the function of FOR20 during mammalian embryonic development remains unknown. To investigate the in vivo function of the For20 gene in mammals, we generated For20 homozygous knockout mice by gene targeting. Our data reveal that homozygous knockout of For20 results in significant embryonic growth arrest and lethality during gestation, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…Consistently, we found that the depletion of either CEP90 or FOPNL decreased the localization at the mother centriole of these distal appendage proteins of about 66% (Figure 6A, B). Altogether, these results suggest that the depletion of either CEP90 or FOPNL prevents the formation of the distal appendages, allowing the understanding of the defective ciliogenesis process previously observed (Wheway et al , 2015; Shen et al , 2020; Sedjaï et al , 2010; Xu et al , 2021). This suggest that FOPNL is a novel and important component for distal appendage assembly.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Consistently, we found that the depletion of either CEP90 or FOPNL decreased the localization at the mother centriole of these distal appendage proteins of about 66% (Figure 6A, B). Altogether, these results suggest that the depletion of either CEP90 or FOPNL prevents the formation of the distal appendages, allowing the understanding of the defective ciliogenesis process previously observed (Wheway et al , 2015; Shen et al , 2020; Sedjaï et al , 2010; Xu et al , 2021). This suggest that FOPNL is a novel and important component for distal appendage assembly.…”
Section: Resultssupporting
confidence: 58%
“…Altogether, these results suggest that the depletion of either CEP90 or FOPNL prevents the formation of the distal appendages, allowing the understanding of the defective ciliogenesis process previously observed (Wheway et al, 2015;Shen et al, 2020;Sedjaï et al, 2010;Xu et al, 2021). This suggest that FOPNL is a novel and important component for distal appendage assembly.…”
Section: The Co-recruitment Of Cep90 Fopnl Ofd1 Is Required For the F...supporting
confidence: 60%
See 1 more Smart Citation
“…Consistently, we found that the depletion of FOPNL decreased the localization at the mother centriole of these distal appendage proteins of about 66% (Fig 6A and 6B). Altogether, these results suggest that the depletion of FOPNL prevents the formation of the distal appendages, allowing the understanding of the defective ciliogenesis process previously observed [26,27,30,31]. This suggests that FOPNL is a novel and important component for distal appendage assembly.…”
Section: Plos Biologysupporting
confidence: 60%
“…Previous work highlighted a role for FOPNL in ciliogenesis, since its depletion in mammalian cells inhibits cilia formation [ 26 ] and FOPNL knockout (KO) mice show embryonic lethality at about E11.5 with an important decrease of cilia in the embryonic node. As a consequence, the embryos show left-right symmetry defects [ 27 ]. However, the dual localization of FOPNL, at both centrioles and centriolar satellites, prevented determining which pool of FOPNL is involved in ciliogenesis, since centriolar satellites are also involved in cilia formation [ 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%